Moznosti ovlivnĕní progrese diabetické nefropatie - Bartos, V (Vnitrni lekarstvi, 1998)
Diabetic nephropathy is a serious microangiopathic complication of diabetes type I and II, which accounts for a marked proportion of the high morbidity and invalidity of diabetics. Although when the disease is fully developed, progression is inevitable, ther are ways how to prevent its development and retard its course. Because reliable prediction of diabetic nephropathy is not possible, primary prevention is essential in all diabetics. It involves, as soon as the diagnosis of diabetes is established, systematic checks of the blood sugar level and permanent satisfactory compensation of diabetes (HbA1c less than 6.5%) which is the main principle during the whole subsequent course of the disease. The principle of secondary prevention the purpose of which is to prevent the development of manifest nephropathy with permanent proteinuria is monitoring of microalbuminuria and maintenance of a normal blood pressure. With regard to pathophysiological associations, in the treatment angiotensin-converting enzymes inhibitors are preferred. The objective of tertiary prevention is to delay renal insufficiency by fortified hypotensive therapy, correction of hyperlipoproteinaemia, dietary protein restriction and satisfactory compensation of diabetes. In case of renal failure dialyzation treatment or transplantation must not be delayed.
Keywords: Humans; Disease Progression; Diabetic Nephropathies; progrese nemoci; diabetické nefropatie; lidé